Designing archaeological memory - Antonello Marotta (City, Territory and Architecture)
Abstract This essay investigates the interplay between archaeology, memory, and architectural renewal, emphasizing the intrinsic connection between historical layers and contemporary design ambitions. Architecture, in its physical manifestation, inevitably transforms into ruins—monuments continuously reshaped by historical context and environmental factors, embedded within the institutions of their origin yet persistently altered by incremental deterioration. Within this perspective, the essay critically examines the influential interpretations by Giovanni Battista Piranesi, John Soane, and Karl Friedrich Schinkel during the eighteenth and nineteenth centuries. Piranesi viewed ruins as catalysts for innovative spatial exploration; Soane embraced architectural fragments as elements of cultural excavation; Schinkel re-envisioned antiquity through integrating the archaeological heritage of Magna Graecia into Berlin's urban fabric, notably with the Altes Museum. Time’s effect on ruins—stripping away ornamental detail to reveal structural purity—further highlights architecture's inherent tectonic qualities. In the twentieth century, archaeological concepts were recontextualized into the internal spaces of architecture, as evidenced by the works of Le Corbusier, Mies van der Rohe, and Louis I. Kahn, who each uniquely engaged with historical traces. Subsequently, in the 1980s, architectural interventions drew explicitly from ancient urban archaeological configurations, notably in Rome’s central archaeological district and Athens’Acropolis. The essay ends with the competition for the Museum Island in Berlin, an iconic city of the twentieth century, where David Chipperfield Architects in 2009 carried out the innovative restoration of the Neues Museum and in 2018 completed the James-Simon-Galerie in the same area. In these interventions, memory is reconstructed, in a dimension that enhances remembrance, recomposes erasures, and opposes the oblivion of a history that has guided the future of our time.